(untitled) (Academia Journal of Medicine, 2023)
This paper explores the application of artificial intelligence in the field of physiotherapy. It delves into the various ways in which AI technologies are revolutionizing the assessment, diagnosis, treatment, and management of musculoskeletal and neurological conditions. The advantages and limitations of AI in physiotherapy are discussed, providing a comprehensive overview of the subject. The paper concludes with a discussion on the future prospects and potential impact of AI on the field of physiotherapy.